Ambivalence and Ambiguity in The Autobiography of Miss Jane Pittman - Monica Michlin (Transatlantica)
This close reading of the text highlights how Miss Jane, in her double role as protagonist and narrator, shows considerable ambivalence towards friend and foe alike, with the result that the apparently transparent ideological meaning of entire episodes is blurred by what some critics have merely put down to “conservatism.” I examine Miss Jane’s almost constant suppression of emotion, and frequent displays of ambivalence towards other black people; her ambiguous relationship to oppressive, but familiar whites like Albert Cluveau or Robert Samson; and her conflicted relation to black heroes and heroics. Is the leading character a variation on the “mammy” who has internalized racist figures of speech, and uses contradictory images that undermine black heroics and validate white oppression? Or is Gaines’s point to undo the “retrick” of heroics and of alienation alike, and, against of backdrop of constant, ordinary destruction of black lives, to cast the adult Miss Jane as a Brer Rabbit-like figure, for whom survival and resistance are both dialectically connected and opposed? Is there a contradiction between her “progress” towards resistance shown in the last section, and her metadiscursive comments in the present, and does her literally walking out of her own story give a conclusive meaning to her narrative, or does it point to the author’s not having been able to resolve the ambivalence and ambiguities within the text?